Measuring Green Banking Practices on Bank’s Environmental Performance: Empirical Evidence from Kathmandu valley - Risal, Nischal; Joshi, Sanjeev Kumar (Journal of Business and Social Sciences, 2018)
The research paper aims to analyze the impact of green banking practices on bank’s environmental performance in Nepal. The casual relational research design has been adopted in the study. The simple and stepwise multiple regression analysis have been performed to accomplish the objective of the research. The research paper follows cross-sectional qualitative research with descriptive outcome. The Chronbach’s Alpha has been used to analyze the reliability of instruments and data. The 189 samples have been collected from the banks using convenience sampling method. The SPSS software has been used to tabulate and analyze the data. The research paper concluded the energy efficient equipment and green policy posed the significant impact on bank’s environmental performance; green loan and green project as not. Similarly, the environmental training contributed mild to bank’s environmental performance. The findings of the paper suggested the role of banks and government in encouraging environmentally sustainable technologies as highly important for increasing bank’s reputation and awareness among customers.